(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the characteristics of management culture and labor relations in Eastern countries. The study examines key cultural values, traditional approaches to leadership, characteristics of employee motivation and organizational ethics, as well as their impact on management practices. Particular attention is paid to comparing these models with Western ones and identifying unique aspects characteristic of Eastern countries such as Japan, China, South Korea, and others. The article emphasizes the importance of understanding cultural contexts for effective management of international teams and business development in the global economy.